Somatosensory temporal discrimination threshold may help to differentiate patients with multiple system atrophy from patients with Parkinson's disease. Issue 4 (24th December 2012) - Rocchi, L.; Conte, A.; Nardella, A.; Li Voti, P.; Di Biasio, F.; Leodori, G.; Fabbrini, G.; Berardelli, A.
<x xml:space="preserve">Abstract</x> Background and purpose Somatosensory temporal discrimination threshold (STDT) is defined as the threshold at which two tactile stimuli applied to the skin are perceived as clearly distinct. The aim of the study was to investigate whether the extent of STDT alterations differs between patients with parkinsonian type multiple system atrophy (MSA‐P) and patients with Parkinson's disease (PD). Possible differences between the two groups may help to differentiate MSA‐P from PD. Methods STDT was investigated in 20 patients with MSA‐P, 21 patients with PD and 18 age‐matched healthy subjects. The clinical evaluation included the Mini‐Mental State Examination, Hoehn and Yahr Scale, Frontal Assessment Battery, Unified Multiple System Atrophy Rating Scale for patients with MSA‐P, and Unified Parkinson's Disease Rating Scale for patients with PD. STDT was investigated by delivering paired electrical stimuli starting with an inter‐stimulus interval (ISI) of 0 ms (simultaneous pair), and progressively increasing the ISIs in 10‐ms steps. Results Between‐group anova showed that STDT statistically differed in MSA‐P versus patients with PD and healthy subjects. Post hoc showed that STDT values in patients with MSA‐P were significantly higher than those in patients with PD and healthy subjects. Receiver operating characteristic curve analysis showed that STDT testing yielded high diagnostic specificity and sensitivity. Conclusions STDT is abnormal in patients with MSA‐P and PD. The degree of STDT abnormalities is higher in patients with MSA‐P than in patients with PD.